Spotting black swans on the horizon, with new mathematical modelling.
The largely unforeseen financial crisis of 2008 made a mockery of much financial modelling. By embracing the dynamism of complex systems, the EU-funded STRIKE project created models built to better cater for the unexpected; from stock market pricing to the true cost of a country joining (and leaving) the EU.